APPLICATION OF X BAND AND S BAND RADAR ON THE SHIP MV BULK CARRIER TO DETECT OBJECTS UNDER THE SURFACE OF THE SEA FOR SHIPPING SAFETY - Muhammad Ismail Chandra; Dety Sutralinda; Antony Dumanik (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2024)
Radio Detection And Ranging or often called RADAR is an electromagnetic wave system used to detect, measure, and find out objects and bad weather within a certain range as long as RADAR can reach it. The purpose of the study was to determine the cause of RADAR in MV. Bulk Carrier cannot detect an object below the surface of the water and To find out the benefits of optimizing X Band and S Band RADAR on MV ships. dear Bulk Carrier This type of research is qualitative descriptive research. This research was carried out on March 16, 2023 at PT. L…P… L… at MV Bulk Carrier The results of the study obtained that X band and S band radars have different capabilities in detecting objects below sea level. X band radars have a shorter detection range but higher resolution, making them more suitable for detecting small objects. S band radars have a longer detection range but lower resolution, making them more suitable for detecting large objects. The use of X band and S band radars on the MV Bulk Carrier is quite effective in detecting objects below sea level, such as corals, obstacles, and submarines. However, there are some obstacles faced, such as interference from sea waves and bad weather. The application of X band and S band radars on the MV Bulk Carrier ship can improve shipping safety by detecting objects below sea level. However, efforts need to be made to optimize its use to make it more effective. Copyright © 20 24 STTAL. - All rights reserved.